Le corps du Prophète - Denis Gril (Revue des Mondes Musulmans et de la Méditerranée)
The body in Islam has a double relationship to the sacred : it is marked by the divine and reflects its presence. The body of the Prophet of Islam was marked at his birth by the signs of his divine election, and further by the visible effects on him of God’s revelation. By its extraordinary nature, the body of the Prophet testifies to his mission even if it is kept veiled. This body gifted with supernatural powers, depicted ingreat detail, symbolises the perfection of this human being. It is deeply venerated by te prophet’s Companions. They kiss it and even absorb its excretions in order to be saved in the afterlife. The eschatological dimensions of contact with this sacred and scented body explain why parts of it, like its sweat or its hair, were venerated AS relics during the life of the Prophet. Although he continues to live, the state of the prophet’s dead body, like those of the martyrs, is for the Muslim community an anticipation of what will become of their bodies in the afterlife : transposed, illuminated. The body of the Prophet is the receptacle of God’s Word and of His presence : it is sacred by his complete union with the Spirit. Among the community of Muslims, the saints are the spiritual heirs of the Prophet, and their bodies reflect this heritage through their luminosity and extraordinary powers. In Islam as in any religious and spiritual tradition, it is necessary to go back to the founding model to understand the relationship between the body and the sacred.